2014
DOI: 10.1002/poc.3306
|View full text |Cite
|
Sign up to set email alerts
|

DFT studies on catalytic dehydrogenation of ammonia borane by Ni(NHC)2

Abstract: The catalytic dehydrogenation mechanism of ammonia borane (NH3BH3, AB) by Ni N‐heterocyclic carbene (NHC) complexes has been investigated by density functional theory. Two possible mechanisms of the dehydrogenation of NH3BH3 have been theoretically studied: intramolecular reaction at Ni dicarbene and intermolecular reaction at Ni monocarbene and dicarbene. The facile occurrence of the dehydrogenation of AB was demonstrated by the low activation barriers of the rate‐determining step. It was found that the intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…First-order rate constants were determined, and KIE experiments indicated that both B-H and N-H bonds were being broken in the rate-determining step(s). This report generated considerable The Catalytic Dehydrocoupling of Amine-Boranes and Phosphine-Boranesinterest with regard to mapping the processes occurring using computational methods [103][104][105][106][107]. In particular the non-innocent role of the NHC ligands, by mediating hydrogen transfer from the amine-borane to the Ni centre, and the role of free carbene in dehydrogenation were revealed.…”
Section: Late Transition Metalsmentioning
confidence: 96%
“…First-order rate constants were determined, and KIE experiments indicated that both B-H and N-H bonds were being broken in the rate-determining step(s). This report generated considerable The Catalytic Dehydrocoupling of Amine-Boranes and Phosphine-Boranesinterest with regard to mapping the processes occurring using computational methods [103][104][105][106][107]. In particular the non-innocent role of the NHC ligands, by mediating hydrogen transfer from the amine-borane to the Ni centre, and the role of free carbene in dehydrogenation were revealed.…”
Section: Late Transition Metalsmentioning
confidence: 96%
“…Analysis of AB reactivity has shown simultaneous two-hydrogen transfers from AB to oxidizing agents and high reactivity of the resulting NB double bond in NH 2 BH 2 . AB’s special reactivity can be attributed to its protic NH hydrogen and hydridic BH hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…) are related to carbon dioxide reduction by ammonia borane, a system of interest to carbon‐neutral chemistry and materials development . The polarized BN and BN bonds have been noted as leading to a wide variety of reactivity, which becomes even more complex as CO bonds are introduced as reactive partners . Compared to the previous SBB examples, significant polarizations during reaction means more basis functions will be needed to capture this reactivity.…”
Section: Resultsmentioning
confidence: 99%